An Analysis of Using Short Movie on Students’ Motivation in Learning English at The First Grade Students’ of SMK N 1 Jambi City - Jihan Salsabila; Yanti Ismiyati; Ridho Praja Dinata (Universitas Batanghari Jambi, 2021)
This study analyzed the use of short movies on student motivation at SMKN 1 Jambi. This study aims to determine the effect of short films on the motivation to learn English in grade I SMKN 1 Jambi. After conducting the interview, the data analyzed by using a phenomenology research design with the use of qualitative research. The usage of the qualitative is used to know about the use of short movie on student motivation in SMKN 1 Jambi. This study can be concluded from 6 students. From the interview results, it is known that the use of short movies in learning English can facilitate the learning process. So it can be seen that the use of short movies can greatly influence students’ motivation.Key Words: Short Movie, Motivation, Learning English.